2018
DOI: 10.1007/s00464-018-6025-3
|View full text |Cite
|
Sign up to set email alerts
|

Adenoma detection rate metrics in colorectal cancer surveillance colonoscopy

Abstract: The major finding of this study is a defined CRC-ADR for HQD based on the ability to achieve S-ADR ≥ 25%. S-ADR strongly correlates with CRC-ADR. CRC-ADR is quite similar to the colonoscopists' respective S-ADR for both HQD and LQD. For colonoscopists who perform limited screening colonoscopies but do perform CRC surveillance colonoscopies, ADR metrics similar to S-ADR to assess quality in colonoscopy could be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 20 publications
0
8
2
Order By: Relevance
“…[ 14 ] Secondary surveillance ADR after colorectal resection for colon cancer was significantly higher than first surveillance ADR colorectal resection for colon cancer. [ 15 ] Moreover, Fuccio et al reported an ADR of 25.2% on second surveillance colonoscopy with a higher rate in those who had left hemicolectomy than right hemicolectomy. [ 9 ] Furthermore, Yun et al also showed that left colon resection had a higher incidence of adenoma than right colon resection in the second surveillance colonoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…[ 14 ] Secondary surveillance ADR after colorectal resection for colon cancer was significantly higher than first surveillance ADR colorectal resection for colon cancer. [ 15 ] Moreover, Fuccio et al reported an ADR of 25.2% on second surveillance colonoscopy with a higher rate in those who had left hemicolectomy than right hemicolectomy. [ 9 ] Furthermore, Yun et al also showed that left colon resection had a higher incidence of adenoma than right colon resection in the second surveillance colonoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…High-quality colonoscopy requires rigorous standards of quality control [6]. The three most commonly recommended colonoscopy key performance indicators (KPIs) are the caecal intubation rate (CIR) [6][7][8], the adenoma detection rate (ADR) [9,10] and the colonoscope withdrawal time (CWT) [6], although the specific KPI calculations and targets vary between different clinical practice guidelines [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Several large population-based studies have evaluated these KPIs for colonoscopy [9,[14][15][16][17][18][19][20][21][22][23]. Some studies included all patients undergoing colonoscopy [14][15][16]18]; however, others elected to exclude patients who have previously had a colonic resection (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several organizations have issued guidelines on individuals or population-based CRC screening and the efforts have contributed more or less to the declined morbidity and mortality of CRC 11 - 14 , the increased annual CRC incidences worldwide highlight the need of developing more effective approaches. On the other hand, currently used screening methods either have uncertain or limited efficiency (e.g., stool-based tests) or are acceptable by few people without symptoms as routine test due to invasiveness, complicate processes and high cost (e.g., colonoscopy) despite its reliable for detection 12 , 15 - 17 . Thus, discovery and development of more reliable and feasible biomarkers, which enable the identification of individuals at high risk or with early CRC who should further undergo colonoscopy, are in urgent need.…”
Section: Introductionmentioning
confidence: 99%